(untitled) (Research, Society and Development, 2022)
Due to the deep economic, political and social crisis faced by Venezuela in recent years, Brazil has become one of the main destinations of Venezuelan indigenous migrants, who came in search of better living conditions. From this context, we aimed to build a productive urban backyard in the Waraos Indigenous Reception Unit in Campina Grande, PB. The activities took place with the participation of all the residents. Fruits, medicinal species and also corn in consortium with fava beans, yuca, sweet potatoes and jerimum were cultivated. The productive backyard in the Reception Unit provides indigenous migrants with the rescue of their original culture outside their territory, leverages the production of multiple products in small spaces, improves quality of life, food security and sovereignty, provides local integration of migrants, therapeutic activity for the elderly, exchange of knowledge and transmission of traditional knowledge to the next generations.